Clinical and functional outcomes of ilizarov bone transport in traumatic tibial bone loss - Mohd Yusof, Nazri; Kow, Ren Yi; Sulong, Ahmad Fadzli; Nallayan, Ramesh@Muthu; Zainal Abidin, Muhammad 'Adil (Malaysian Orthopaedic Association, 2025)
Introduction: Bone loss is a serious complication following an open fracture or fracture-related infection in the tibia. Treatment with Illizarov bone transport in this condition is preferred because it minimises additional soft tissue injury and is able to close the bone and soft tissue defects through distraction osteogenesis. The objective of this study is to evaluate the relationship between functional outcomes of patients with tibial bone loss treated with Illizarov bone transport and return to work. Materials and methods: A cross-sectional study among 40 patients was carried out in 2 public hospitals. Patient records and radiographs were reviewed for information on the initial injuries, treatment, union of bone, and complications while on treatment. The clinical outcomes were evaluated with ASAMI Bone grading system while the functional outcome of the affected limb was assessed using Lower Extremity Score (LEFS) and ASAMI Functional grading system at least 10 months after the removal of the Illizarov external fixator. Results: Thirty-eight (95%) achieved union. Thirty-six (90.0%) patients had excellent and good scores for clinical and functional results, respectively using the ASAMI grading system. The mean LEFS is 80.1% (range 58 to 91%). Thirty-three (82.5%) patients were able to return to work. The clinical outcome has a strong and positive correlation with functional outcome both on ASAMI functional score and LEFS (p<0.001). Patients with good and excellent ASAMI functional scores significantly correlate with higher odds to return to work (p<0.001). Return to work was also associated with a higher LEFS score (p=0.006). Conclusion: Most patients with tibial non-union treated with Illizarov bone transport have good and excellent clinical and functional outcomes and are able to return to work. Return to work significantly correlates with good functional outcomes